Rejection, adoption or conversion: the three ways of being a young graduate auto-entrepreneur. (1st December 2016) - Elsa Vivant
Abstract : This article is based on the results of a survey on the use of the new French fiscal regime for small scale business: the Auto-entrepreneur plan. The survey focused on young graduates entering the job market by enrolling in this plan. The article investigates how they adapt to their new situation and finds that auto-entrepreneurs have ambivalent feelings that expose the plan's ambiguities: does it support business creation (and entrepreneurship) or just provide training in entrepreneurial labour? The analysis of the respondents' discourse and the accommodations they make reveals the multiple uses and meanings of the Auto-entrepreneur plan as graduates create identities for themselves and for others in the process of navigating a path through employment, activity, independence and professionalism. Three ideal-typical patterns of the young graduates' social uses of the Auto-entrepreneur plan are identified and discussed: the 'independent salaried worker', the 'entrepreneurial unemployed worker' and the 'convert entrepreneur'. This categorisation sheds light on the processes of what appears to be a conversion to entrepreneurial labour, prior to entrepreneurship. Entering the workforce through the Auto-entrepreneur plan promotes a learning and internalisation of new standards of working behaviour, those of entrepreneurial labour (self-promotion, availability, self-learning, adaptation to market constraints, autonomy and accountability) that result in accepting a high degree of insecurity and loss of rights. Faced with this entrepreneurial mandate, each young graduate reacts differently: rejection, adoption or conversion.